TREE-FERNS OF THE GENUS CYATHEA IN JAVA - R. E. HOLTTUM (BRIN Publishing (Penerbit BRIN), 1965)
A full taxonomic study of the genus Cyathea has recently been published in Flora Malesiana (Ser. II, vol. 1, part 2, Dec. 1963). In that work the genus is construed in a broad sense, to include Alsophila and Hemitelia (also Gymnosphaera and Schizocaena of Copeland's Genera Filicum), the total number of species being 191, and a new subdivision of this comprehensive genus is proposed. The keys in Flora Malesiana, dealing with such a large number of species, are complex, and not very easy to use for local purposes. I have therefore made a simpler key to cover the species of java only, and hope this will be of service to botaniists in Java.